A prática da governança colaborativa na formulação de políticas públicas de saúde no Brasil - Ramos, Sandra Silvéria (2024)
The public health system in Brazil was organized só that all citizens have equal access to the public health service, and that this service is guaranteed by the state. This assumption is established in the Federal Constitution of 1988, a rule that also established the Brazilian Unified Health System, the SUS, financed by the Union, States, Federal District and Municipalities. The SUS is a set of health actions and services provided by federal, state and municipal public bodies and institutions, direct and indirect administration and foundations maintained by public authorities, a concept given by Organic Health Law No. 8,080, published on 19 September 1990. The Unified Health System requires joint management by federal, state, district and municipal governments, to formulate public policies that provide services for the promotion and recovery of health. The structure of the system includes collegiate negotiation and decision-making bodies involving managers, providers, health professionals and users from the three spheres of government. In this organization, the Ministry of Health plays a leading role, within the Union, and the Health Departments at the state, district and municipal levels. Collaboration between actors involved in the practice of public health governance in Brazil in a collaborative manner is an indispensable factor in meeting social demands in a country with extensive and diverse territoriality in social, economic, cultural and environmental aspects, given government budget restrictions in recent times due to the dynamics of the global economy and unforeseen events, such as the Covid-19 Pandemic. Reflecting on the topic of collaborative governance and the formulation of public health policy is relevant to subsidize the challenges inherent in the area and obtain more efficient results in the formulation of such policies. Thus, the research seeks to understand how the practice of collaborative governance established in the SUS contributes to the more efficient formulation of public policies. Based on the conceptual debate on collaborative governance and efficiency in the formulation of public policies, documentary data is also collected, particularly from the minutes of the meetings of the tripartite intermanagement committee to develop the research, which characterizes it as a qualitative approach, applied and directed purpose for exploratory and descriptive objectives. The main results demonstrate the existence of requirements and cooperation regimes between the actors responsible for formulating and agreeing on public health policies at the federal level, however, aspects related to the formal organization of the deliberative body must be improved.